PENYEMBUHAN LUKA PERINEUM PADA IBU NIFAS DENGAN MENGGUNAKAN EKSTRAK SIDAGURI (SIDA RHOMBIFOLIA): Healing Of Perineal Wounds In Postpartum Women Using Sidaguri Extract (Sida Rhombifolia) - Kasmiati (LPPM - STIKES Pemkab Jombang, 2023)
Infection during the postpartum period is still a big problem for postpartum mothers during the postpartum period, data show that 50% of nifas women experience infection, and every day one postpartum woman experiences infection due to perineal lacerations. This study aims to determine the healing of perineal wounds in postpartum mothers using Sida Rhombifolia extract in the working area of ??the Watampone Health Center and BPS Hj Harfiani. This type of experimental research with accidental sampling method with a total sample of 36 people, the instruments used were questionnaires and perineal wound healing assessment checklist. Statistical tests show the results of the Independent T-test intervention group mean value of 3.000 standard deviations of 0.000 control mean value of 2.384 standard deviations of 0.650 with a P-Value of 0.00 based on this shows the results of the intervention sample given sidaguri (sida rhombifolia) extract and also not taking antibiotics has a greater effect compared to controls who are not given sidaguri (sida rhombifolia) extract by taking antibiotics. ) ). So that this research can be used as an alternative in accelerating the healing of perineal wounds for postpartum mothers to reduce the incidence of perineal wound infections.